The Implementation of Google Classroom to Teach English Nursing in Pandemic Era Covid19 - Fini Widya Fransiska (Universitas Lancang Kuning, 2022)
Online learning during the pandemic of COVID-19 is one the biggest challenge for the teachers and students to achieve the goals of learning optimally, including the goals of English Language Communicative Competencies. One of the alternatives of learning technology can be applied was Google Classroom Application to teach English virtually. This application has lots of benefits that can be optimized to design various interesting and fun English learning activities outside the classroom. Many learning strategies can be applied by using various features in Google Classroom such as sharing document, photo, audio/video file. The purpose of this study is to know how is the implementation of Google Classroom to teach English Nursing in pandemic era COVID 19 . This study focused on four aspect. Teacher preparation, implementation of teaching, evaluation and the last students response. The reseacher use four instruments are interview, observation, documentation and students response. For preparation the teacher use lesson plan when she teach the students, for implementation the teacher also use English when she explain the material,for evaluation the teacher give conclussion for material which them and sometimes the teacher give them homework and they must sumbit in Google Classroom.